2019
DOI: 10.1111/pce.13539
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the vertical distribution of leaf area enhanced light interception efficiency in maize over generations of selection

Abstract: Breeders select for yield, thereby indirectly selecting for traits that contribute to it. We tested if breeding has affected a range of traits involved in plant architecture and light interception, via the analysis of a panel of 60 maize hybrids released from 1950 to 2015. This was based on novel traits calculated from reconstructions derived from a phenotyping platform. The contribution of these traits to light interception was assessed in virtual field canopies composed of 3D plant reconstructions, with a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 46 publications
4
67
0
2
Order By: Relevance
“…Water shortage limited elongation and expansion growth, moisture content and photosynthesis of leaves, which influences on the growth and development of maize plant (Duvick and Cassman, 1999;Zhang et al, 2019). The morphological changes are observed in maize hybrids released over different generations in American (Duvick and Cassman, 1999), European (Perez et al, 2019) and Chinese (Ma et al, 2014) projects. The number of leaves per plant increased and the leaf area index tend to be higher for modern hybrids than older ones.…”
Section: Discussionmentioning
confidence: 99%
“…Water shortage limited elongation and expansion growth, moisture content and photosynthesis of leaves, which influences on the growth and development of maize plant (Duvick and Cassman, 1999;Zhang et al, 2019). The morphological changes are observed in maize hybrids released over different generations in American (Duvick and Cassman, 1999), European (Perez et al, 2019) and Chinese (Ma et al, 2014) projects. The number of leaves per plant increased and the leaf area index tend to be higher for modern hybrids than older ones.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) A second possible use of this model is to simulate the consequences of plant architecture traits on light interception. We have recently shown that changes in distribution of leaf area along leaf ranks allowed a genetic progress of the amount of light intercepted by the canopy layer hosting maize ears ( Perez et al , 2019 ). Finally, the 10 genotype-dependent parameters of the model may be predicted via genomic prediction based on a set of platform experiments such as those in Dataset C, thereby allowing one to predict the leaf area of hundreds of genotypes from their genotypic markers in hundreds of fields, as recently carried out for flowering time ( Li et al , 2018 ) or for the responses of yield to environmental conditions ( Millet et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, the final leaf number ( N final ) is closely related to the duration (number of plastochrons) from plant emergence to the floral transition of the shoot apex, but also to flowering time ( Parent et al , 2018 ). Hence, flowering time indirectly affects final leaf area, the vertical distribution of leaf area, and that of light interception ( Perez et al , 2019 ). Most models take these effects into account via the duration of leaf growth as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 1.5, the same Binarize fragment is reused and the 3D reconstruction fragment is added to reconstruct the volume of the 1,680 plants in 3D. This SWf reuses the same Binarize segment to reconstruct the volume of the 1600 plants in 3D (3D reconstruction fragment) and compute the light intercepted by each plant placed in a virtual scene reproducing the canopy in the glasshouse ( [6,26]). Finally, in the SWf shown in Figure 1.6, the previous SWf is reused by Chen et al ( [8]), but with different parameters to study the environmental versus the genetic influence of biomass accumulation.…”
Section: Use Case In Plant Phenotypingmentioning
confidence: 99%